PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR - Novieyanti, Ira Ayu; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is aimed to test the influence of mechanism of good corporate governance to the earnings quality. This research the mechanism of good corporate governance has been measured by using managerial ownership, institutional ownership, board of independent commissioner, and audit committee. Managerial ownership is measured by the percentage of the stock which is owned by the management. Institutional ownership is measured by percentage of stock which is owned by the institution from outside of the company. Board of independent commissioner is measured by the percentage of board of commissioner from outside of the company. Audit committee as the dummy variable with the value 1 if the numbers of audit committee are 3 people and the value is 0 when it is less than 3. The earnings quality has been calculated by using modified Jones model i.e. Discretionary Accrual (DA). The result of this research shows that managerial ownership and audit committee has positive influence to the earnings quality. Meanwhile, institutional ownership and board of independent commissioner does not have any influence to the earnings quality.Keywords: managerial ownership, institutional ownership, board of independent commissioner, audit committee, earnings quality